Knowledge, Attitude and Practices on Family Planning Among Women Receiving Antenatal Care at University of Nigeria Teaching Hospital Enugu - Okoye, Stella O; Udem, Ngozi D; Ezenduka, Charles C (British Journal of Healthcare and Medical Research, 2024)
Family planning is the practise of controlling the number of children one has and the intervals between their births, particularly by means of contraceptive or voluntary sterilization. Ability of women to space and limit her pregnancies has a direct impact on her health and well-being as well as on the outcome of each pregnancy. Contrary poor family planning practices has excessive burden on family budget which in many cases leads to poor quality of life in various aspects such as health, education, environment and housing.The aim of this study is to assess the knowledge, attitude and practices of family planning among women receiving antenatal care at University of Nigeria Teaching Hospital Enugu. The study was conducted by using a pre-tested, structured self administered questionnaire for four months between the periods of June to September 2022 in University of Nigeria Teaching Hospital, Ituku Ozalla, Enugu, Nigeria. The level of knowledge, attitude and practise of family planning were elicited from the questionnaire as well as factor affecting it. Most of all the women had knowledge of family planning/contraceptives (98.6%). Their sources of information were majorly through TV/radio (52.2%). Though the attitude of the women to facts of family planning information was poor (40.3%), most women still practiced family planning methods (87.0%). Withdrawal, natural and behavior, injectables and barrier were the most adopted methods. The factors such as desire for children, side effects/ fear of complication and lack of knowledge of modern methods affect usage of family planning. The level of knowledge of family planning among the pregnant women was high (98.6%) and most women practiced family planning methods (87.0%)